Seronegative disseminated Bartonella spp. infection in an immunocompromised patient - Weilg,Claudia (2016)
An 11 year old, hispanic girl with a history of B-cell acute lymphoblastic leukemia was admitted to the hospital for symptoms compatible with Bartonella henselae infection. The first molecularly diagnosed case of disseminated Bartonella henselae infection was reported in an immunocompromised patient in Lima, Peru. The analysis was confirmed by Polymerase Chain Reaction and automated sequencing of a liver biopsy sample, even though the serologic tests were negative. In conclusion, Bartonella spp. infection should have a particular diagnostic consideration in immunocompromised patients with fever of unknown origin and further investigation regarding the patient's past exposures with cats should also be elicited.